1978
DOI: 10.1161/01.res.43.5.777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetylcholine on the ventricular specialized conducting system of neonatal and adult dogs.

Abstract: SUMMARY We determined the effects of acetylcholine on automaticity of isolated cardiac Purkinje fibers from neonatal and adult dogs and on the idioventricular rhythm of adult dogs with complete atrioventricular block. Isolated Purkinje fibers were studied with standard microelectrode techniques during superfusion with Tyrode's solution at 37 °C. For both age groups, spontaneous rate was' decreased by acetylcholine, an effect which was reduced by atropine. The magnitude of the effect is equal in both neonatal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…First, in addition to the dominant cardiac cholinergic (muscarinic) M2 receptor found in the adult heart, M1 subtypes may be found in the neonatal heart (43). These neonatal receptors may serve different physiologic responses to acetylcholine stimulation (44). Second, parasympathetic activity can modulate sympathetic effects by inhibiting norepinephrine release and modulating the sympathetic system (45).…”
Section: Autonomic Function In Preterm Infantsmentioning
confidence: 99%
“…First, in addition to the dominant cardiac cholinergic (muscarinic) M2 receptor found in the adult heart, M1 subtypes may be found in the neonatal heart (43). These neonatal receptors may serve different physiologic responses to acetylcholine stimulation (44). Second, parasympathetic activity can modulate sympathetic effects by inhibiting norepinephrine release and modulating the sympathetic system (45).…”
Section: Autonomic Function In Preterm Infantsmentioning
confidence: 99%
“…However, there are conflicting data regarding the importance of direct vagal effects in the ventricular myocardium and the HPS. Several studies have shown that vagal stimulation and ACh infusion exert a negative chronotropic effect on His-Purkinje tissues in vitro and in vivo (52,(60)(61)(62)(63). In addition, ventricular refractory periods are shortened in response to atropine in patients pretreated with propranolol, suggesting a direct cholinergic effect in this tissue (64).…”
Section: Autonomic Effects On the Hpsmentioning
confidence: 99%
“…In addition, carotid sinus massage does not allow stable slow rates, but rather, prolonged pauses of unpredictable length with no possible control of the preceding cycle length. Another problem is the possibility that the liberation of acetylcholine might eventually alter some of the variables under study.29 31 Nevertheless, vagal stimulation is the most accessible way of slowing instantaneously the heart rate in the human, and the proposed model, despite its limitations, is practically the only manner of studying the effects of drugs on In addition to its theoretical interest regarding the mechanisms of tachycardia-and bradycardia-dependent block, our study suggests that isoproterenol may be useful in some patients with left BBB in which there is a need to observe the normally conducted QRS pattern, in patients in whom a complete interruption of conduction in one of the bundle branches must be ascertained, and in patients in whom phase 4 block is suspected. …”
Section: Effects On Refractoriness and Conductionmentioning
confidence: 99%